Analisis Pemasaran Syariah Pembiayaan Cicil Emas Bank Syariah Indonesia KCP Bangkalan Trunojoyo - Ahmad Muharram Alafi; Trischa Relanda Putra (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2024)
This research aims to identify the marketing strategies implemented by Bank Syariah Indonesia KCP Bangkalan Trunojoyo in marketing gold installment financing products and to increase the number of customers for these products. This research uses a qualitative descriptive approach, with data processing using Nvivo software and analyzed using the reduction method. The research results reveal that Bank Syariah Indonesia KCP Bangkalan Trunojoyo has succeeded in adopting the 4C Marketing Mix concept in its marketing strategy. The bank has also discovered variables that influence consumer choices for gold installment financing products. This includes cultural, social, economic, and psychological preferences that influence their purchasing decisions. This shows that understanding customer needs and desires with a comprehensive and organized approach is very important for the success of marketing sharia products.